Azahelicenes as visible light photoinitiators for cationic and radical polymerization: Preparation of photoluminescent polymers and use in high performance LED projector 3D printing resins. Issue 7 (6th January 2017) - Al Mousawi, Assi; Dumur, Frédéric; Garra, Patxi; Toufaily, Joumana; Hamieh, Tayssir; Goubard, Fabrice; Bui, Thanh‐Tuân; Graff, Bernadette; Gigmes, Didier; Pierre Fouassier, Jean; Lalevée, Jacques
ABSTRACT: In this article, novel azahelicenes (AZs) were synthesized and proposed as high performance visible light photoinitiators for both the free radical polymerization of acrylates and the cationic polymerization (CP) of epoxides upon visible light exposure using Light Emitting Diodes (LEDs) @405, @455, and @470 nm. Excellent polymerization initiating abilities are found and high final conversions were obtained. Remarkably, an exceptional long lifetime photoluminescence property of the polymer films was observed when synthesized in presence of AZs. A full picture of the involved chemical mechanisms is given. AZs being high performance photoinitiators, their use in new cationic LED 3D printing resins will be also presented, that is, the cationic process upon LED projector @405 nm can be useful to reduce the shrinkage usually observed for radical polymerization. LED projector printing is very interesting compared to laser writing as this technology projects the profile of an entire layer of a 3D object at one time. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 55, 1189–1199 Abstract : Azahelicenes having strong visible light absorptions are presented as photoinitiators for radical and cationic polymerization reactions upon violet and blue LEDs. Their use in new cationic LED 3D printing resins is provided.